2018
DOI: 10.1123/ijsnem.2017-0293
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beetroot Juice Supplementation on Dynamic Apnea and Intermittent Sprint Performance in Elite Female Water Polo Players

Abstract: Nitrate-rich beetroot juice is thought to have ergogenic effects, particularly in conditions where oxygen availability is limited. Whether these effects also apply to elite athletes is currently unknown. The aim of this study was to assess the effects of beetroot juice supplementation on dynamic apnea and intermittent sprint performance in elite female water polo players. In a double-blinded, randomized, crossover manner, the Dutch National female water polo team (N = 14) was subjected to two 6-day supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
3
21
0
1
Order By: Relevance
“…The principal original findings of this study were that 3-days of BRJ juice supplementation, which increased plasma nitrite concentration and lowered systolic blood Compared to the PLA condition, plasma nitrite concentration was 289% higher in the BRJ condition. This result is consistent with numerous previous studies 16 , including the study by Jonvik et al 4,19 in elite female water polo athletes. Therefore, the BRJ intervention was successful at increasing the circulating reservoir for O2-independent NO generation by a magnitude that has previously been shown to enhance performance 4 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The principal original findings of this study were that 3-days of BRJ juice supplementation, which increased plasma nitrite concentration and lowered systolic blood Compared to the PLA condition, plasma nitrite concentration was 289% higher in the BRJ condition. This result is consistent with numerous previous studies 16 , including the study by Jonvik et al 4,19 in elite female water polo athletes. Therefore, the BRJ intervention was successful at increasing the circulating reservoir for O2-independent NO generation by a magnitude that has previously been shown to enhance performance 4 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, swimming exercise provokes exercise-induced arterial hypoxemia 15 and since the ergogenic effect of NO3supplementation appears to be more pronounced in hypoxia compared to normoxia 16 , likely as a function of enhanced reduction of NO2to NO 17 , NO3supplementation might represent an effective ergogenic aid for swimmers. In addition, swimming is accompanied by periods of dynamic apnea [18][19][20] , with apnea duration linked to swimming performance 21 . Since there is some evidence that NO3supplementation might enhance dynamic apnea performance [18][19][20] , this might also contribute to a potential improvement in swimming performance following NO3supplementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only two studies investigated the effect of short-term BRJ supplementation in relation to training in well-trained women. A study from Jonvik et al (2017) showed that in elite female water polo-players, BRJ does not improve intermittent sprint performance . The other study showed no reduction in submaximal exercise VO 2 or TT performance after short term BRJ consumption .…”
Section: Well-trained Womenmentioning
confidence: 99%